Non-genomic oestrogen receptor signal in B lymphocytes: An approach towards therapeutic interventions for infection, autoimmunity and cancer. (July 2016) - Seto, Karsen; Hoang, Minh; Santos, Thaddeus; Bandyopadhyay, Mausumi; Kindy, Mark S.; Dasgupta, Subhajit
Graphical abstract: Intracellular signal pathways from plasma membrane bound oestrogen receptor (mER) and GPR30 in B cells. The ligands related and unrelated to oestrogen induce intracellular signals through mER and GPR30 to activate downstream cytoplasmic molecules. The signal pathways are shared with B cell receptor (BCR). A cross talk with different signal pathways is involved. The solid line arrowheads indicate reported track of signal while the dotted line arrowheads indicate most possible connections and proposition for future research. Highlights: Membrane bound oestrogen receptors regulate B cell signalling. Membrane bound PLC and PIP2/IP3 initiate B cell signalling. Fc receptor-like integral protein receptor modulate BCR signalling. BCR signalling initiates Akt, MAP kinase and mTOR pathways. Choice of ligands have importance on cross-talk between receptor-mediated signalling. Abstract: The non-genomic membrane bound oestrogen receptor (mER) regulates intracellular signals through receptor-ligand interactions. The mER, along with G-protein coupled oestrogen receptor GPR 30 (GPER), induces diverse cell signalling pathways in murine lymphocytes. The mER isoform ER-alpha46 has recently been demonstrated in human B and T lymphocytes as an analogue receptor for chemokine CCL18, the signalling events of which are not clearly understood. Ligand-induced mER and GPER signalling events are shared with BCR, CD19 mediated intracellular signalling through phospholipase C, PIP2/IP3/PI3 mediated activation of Akt, MAP kinase, and mTOR. Oestrogen has the ability to induce CD40-mediated activation of B cells. The complete signalling pathways of mER, GPR30 and their interaction with other signals are targeted areas for novel drug development in B cells during infection, autoimmunity and cancer. Therefore, an in depth investigation is critical for determining shared signal outputs during B cell activation. Here, we focus on the mode of action of membrane bound ER in B cells as therapeutic checkpoints.